Antischistosomal and anti-inflammatory activity of garlic and allicin compared with that of praziquantel in vivo - Dina M. Metwally; Ebtesam M. Al-Olayan; Mohammad Alanazi; Sanaa B. Alzahrany; Abdelhabib Semlali (BMC, 2018)
Abstract Background Schistosomiasis is an acute and chronic zoonotic parasitic disease caused by trematode worms. The host inflammatory response to schistosome eggs leads to perioval granulomata formation, mainly in the liver and intestine. This study investigated the potential antischistosomal and anti-inflammatory activity of both garlic extract and allicin on liver fibrotic markers in BALB/c mice with schistosomiasis (S. mansoni infection) compared with that of the commonly used drug, praziquantel (PZQ). Methods In this study, 140 female BALB/c mice (7-weeks old) were divided into seven groups with 20 mice each. Six groups were infected with S. mansoni cercariae and treated with garlic, allicin, or PZQ. The seventh group was the negative control. Twenty-four hours after the final treatment, the mice were euthanised and perfused for worm recovery. The liver and intestines were harvested for parasitological and histological assessment and to analyse the proinflammatory cytokine mRNA expression. Results Prophylactic administration of garlic and allicin to the infected mice significantly reduced the worm burden. Serum concentrations of liver fibrosis markers and proinflammatory cytokines were also reduced. PZQ was the most efficacious for reduction in the number of worms. These results are similar to those normally obtained using PZQ. Conclusions Crushed garlic homogenate and allicin are potential complementary treatments that may be used with PZQ.